Assessment of fruit bats and its food preferences in Mt. App Natural Park, Kidapawan City, North Cotabato, Philippines - Relox, Richel E.; Florece, Leonardo M.; Baril, Joselito A.; Coladilla, Jesusita O. (2014)
Fruit bats are important seed dispersers that aid in natural forest regeneration in degraded areas. This study assessed fruit bat species in a portion of Mt. Apo, Kidapawan City, North Cotabato from Septembe to December 2010 covering six habitat types: human settlement area/residential area, agro-ecosystem/cultivated area, secondary forest/reforested site, forest edge, riverine/riparian area and montane forest for 1,118 net night hours. The food habits of the bats were also determined based on fecal examination and dropped fruits, which were verified through secondary information using indigenous knowledge interviews. A total of five bat species were noted such as Cynopterus brachyotis (n=83), Haplonycteris fisheri (n=33, Ptenochirus minor (n=25), Macroglossus minimus (n=20) and Ptenochirus jagori (n=12) wherein almost 50% of these are Philippine endemics and could be considered as seed dispersers of diverse trees. This study recommends the protection of Philippine and Mindanao endemic fruit bats such as P. minor, H. fischeri and P. jagori, through the conservation of their staple food (Ficus species) and the remaining primary forest habitat.
Keywords: Fruit bats; Food habits